2010
DOI: 10.1525/auk.2010.09014
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Boubou (Malaconotidae:Laniarius) From the Albertine Rift

Abstract: Résumé.-Nous décrivons ici Laniarius willardi, une nouvelle espèce de la famille des Malaconotidae vivant au Rift Albertine, en Afrique. Le caractère morphologique le plus remarquable de cette espèce est un iris gris à bleu-gris. Ceci et des données morphométriques externes indiquent que L. willardi est différent des autres Laniarius. De plus, L. willardi est génétiquement différent et son plus proche parent est L. poensis camerunensis, au Cameroun. L. atrococcineus et L. leucorhynchus forment le clade saeur d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Several studies have highlighted dispersal in the diversification of tropical birds and mammals across the Albertine Rift (Voelker et al . , Engel et al . , Roy et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have highlighted dispersal in the diversification of tropical birds and mammals across the Albertine Rift (Voelker et al . , Engel et al . , Roy et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that individuals dispersed via streams, at least locally. Several studies have highlighted dispersal in the diversification of tropical birds and mammals across the Albertine Rift (Voelker et al 2010b, Engel et al 2014, Roy et al 2014, Demos et al 2015, and it seems implausible that all Albertine Rift montane swamp habitats were ever directly connected; hence, dispersal must have played a role. Our data suggest that divergence was initiated not more than 170 thousand years ago.…”
Section: Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…New vertebrate species are still being described from the area, including birds (Engel et al 2014), small mammals (Kerbis Peterhans et al 2013a, 2013b, lizards (Greenbaum et al , 2012, and amphibians (Evans et al 2011, Greenbaum et al 2013, Portillo and Greenbaum 2014a, 2014b. Voelker et al (2010) showed that sooty bush-shrikes in the genus Laniarius that occur in mid-elevation forests in the Albertine Rift are morphologically and phylogenetically distinct from those that inhabit higher-elevations forests. They described the mid-elevation taxon as Laniarius willardi (Willard's Sooty Boubou), which is also vocally distinct (recordings deposited in xeno-canto: http://www.xeno-canto.org/).…”
Section: Introductionmentioning
confidence: 99%